Authority to Cancel The Judge Agreement as Evidence of Cancellation of Grants Authentic Act and Sale Agreement - Umar Al Faruq; Akhmad Khisni (Jurnal Akta, 2018)
This study aimed to analyze the authority of the judge, analyze the civil law, and to determine the factors that are considered by the judge in dismissing the notarial agreement as authentic evidence regarding the cancellation of the grant agreement and the agreement of sale. Authentic agreement is a legal cover, which had a value of legal certainty and the strength of evidence that is perfect for the parties to make. The existence of an authentic agreement due to provisions. legislation that would require such evidence to certain legal acts of the parties calls for certain legal actions embodied in the form of an authentic agreement. As for the issues that arises is how power law Notary agreement as evidence and what criteria which determine the handicap of a notarial agreement so that it can be canceled by the court. This research is research Empirical research juridical or legal research library (library research). Data were analyzed using qualitative research, is sorting and preparation of data classification, editing data and coding data for building performance analysis data, conduct data analysis in accordance with the construction of the discussion of the research results.Keywords: Judge Authority; A Notary; The Authentic Act Of Cancellation; The Grant Agreement; Sale Agreement.